Efeitos de uma tecnologia educativa na autoeficacia para amamentar e no aleitamento materno exclusivo aos dois meses de vida da criança - Javorski, Marly (2014)
The exclusive breastfeeding until the child is six months old it’s contribute to the child and mother health promotion. However, many mothers interrupt the exclusive breastfeeding because of the lack of confidence to breastfeed. The maternal self-efficacy to breastfeed it’s a strong risk predictor for weaning. Therefore, the health education based on the self –efficacy concept may favor the exclusive breastfeeding. Thus, this research had as objective to evaluate the impact of a show album “I can breastfeed my sun” in the maternal self-efficacy to breastfeeding, in the prenatal and postnatal period, and its repercussion in the exclusive breast feeding in the first second two months of child life. It’s about an randomized controlled clinical trial performed with 112 pregnant women in the third semester of gestation, distributed randomly between intervention group (IG) and control group (CG). The intervention was characterized based on health education using a show album in the IG and the effects compared with the CG pregnant women. The data collection was performed through interviews in the prenatal period and by phone calls in the second, fourth and sixth week postpartum. We used the Breastfeeding Self-Efficacy Scale: Psychometric Assessment of the Short Form (BSES-SF) to measure the self-efficacy scores. Beyond the BSES-SF were used three forms to investigate the socioeconomic profile, obstetric history and current pregnancy; variables associated with parturition, birth and child feeding; and the child dietary pattern in the first two months of life. In the analyses we used descriptive statistics; bivariate by comparison ratio test and averages; and the evaluation of relative risk. It was observed the homogeneity between the groups in basis such as socioeconomic variables and breastfeeding experience. There was no difference between the BSES-SF scores, before the intervention, among the groups (p-0,408). It was found important statistic difference in the average score of self-efficacy among IG women when compared with CG (p<o,oo1), in the second, fourth and eighth week postpartum. The probability of IG women to reach high self-efficacy scores in the eighth week postpartum was bigger than in the CG (RR 1,4; IC 1.13-1,68). It has also been found an important statistic difference (p<0,001) in the exclusive breastfeeding rate between the groups at the eighth week postpartum, the probability to exclusive breastfeeding in the IG was twice as bigger than in the CG (RR 2,2 IC 1,51-3,21). The exclusive breastfeeding in IG primiparous was also bigger than in the CG (RR 2,7 IC 1,37-5,23). The study results indicate that a show album educative intervention, elaborated from the breastfeeding self-efficacy concept, applied to pregnant women positively reverberated in the self-efficacy to breastfeeding and in the maintenance of exclusive breastfeeding in IG women. Furthermore, it was observed the positive association between the self-efficacy scores and the higher rates of exclusive breastfeeding in the first two months of a child life.